2001
DOI: 10.1046/j.1365-2214.2001.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

‘If I had a friend in a wheelchair’: children's thoughts on disabilities

Abstract: The purpose of the present study was to examine what notions there are among ordinary preschool children and schoolchildren about physically handicapped children using wheelchairs. Forty-eight children-16 children of preschool age (half boys, half girls, aged around 6), 16 children in primary school class 2 (half boys, half girls, aged around 8) and 16 children in class 4 (half boys, half girls, aged around 8)-constituted the investigated group. The method used was a combination of drawings produced by the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
2
32
2
14
Order By: Relevance
“…However, it also provides support to the findings of Tamm and Prellwitz (2001) who found that children between the ages 6-10 perceived children sitting in a wheelchair to be injured.…”
Section: Pre-program Perceptions Of Dance Ability and Disabilitysupporting
confidence: 68%
See 2 more Smart Citations
“…However, it also provides support to the findings of Tamm and Prellwitz (2001) who found that children between the ages 6-10 perceived children sitting in a wheelchair to be injured.…”
Section: Pre-program Perceptions Of Dance Ability and Disabilitysupporting
confidence: 68%
“…Moreover, he began playing frequently with Dillon. Perhaps consistent with Tamm and Prellwitz (2001) Dillon perceived Logan as someone who was hurt but got better since he did not need his walker any more.…”
Section: Post-program Perceptions Of Dance Ability and Disabilitymentioning
confidence: 59%
See 1 more Smart Citation
“…This has been supported with adults (Hunt and Hunt 2000;Seo andChen 2009), adolescents (McDougall et al 2004) and young children (Panek and Smith 2005). However, Tamm and Prellwitz (2001) found that females and males were about equal in their views toward individuals with disabilities. Attitudes toward individuals with disabilities can vary as a function of many variables, such as culture, demographics, type of disability, age, and gender (Deal 2003).…”
Section: Discussionmentioning
confidence: 79%
“…It is recommended that participation among children with hearing/visual impairments should be further evaluated in adolescence as well. In the case that limited participation in early childhood is more restricted in adolescence, special efforts should be made by families, educators and decision makers to minimize social isolation and passive life style, and maximize involvement in activities in order to enhance child's development and quality of life King, Cathers, Miller Polgar, MacKinnon, & Havens, 2000;Tamm & Prellwitz, 2001).…”
Section: Enjoymentioning
confidence: 99%